2000
DOI: 10.1183/09031936.00.16590100
|View full text |Cite
|
Sign up to set email alerts
|

Lung sounds in asbestos induced pulmonary disorders

Abstract: The aim of the study was to compare the lung sounds in patients with asbestos related pulmonary disorders with findings in high-resolution computed tomography (HRCT), and with lung function variables, in order to find out associations of acoustic changes with radiological fibrosis, emphysema or with pulmonary gas transfer functions.Sixty-four patients with asbestos-related pleural disease, with or without pulmonary disease, were studied. Lung sound recording and analysis was carried out with a computerized lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
1
2
0
1
Order By: Relevance
“…Th e frequency of normal respiratory sounds was found to be higher during inspiration than expiration (17). Th is fi nding is in line with previous literature describing the normal respiratory sounds of healthy people (26) and of people with chronic diseases, such as bronchiectasis, fi brosing alveolitis and asbestos-related pleural disease (17,27). Normal respiratory sounds at the trachea presented higher frequencies than sounds at the posterior chest.…”
Section: Discussionsupporting
confidence: 88%
“…Th e frequency of normal respiratory sounds was found to be higher during inspiration than expiration (17). Th is fi nding is in line with previous literature describing the normal respiratory sounds of healthy people (26) and of people with chronic diseases, such as bronchiectasis, fi brosing alveolitis and asbestos-related pleural disease (17,27). Normal respiratory sounds at the trachea presented higher frequencies than sounds at the posterior chest.…”
Section: Discussionsupporting
confidence: 88%
“…British investigators have reported that detecting crackles on time-expanded waveform analysis was equivalent to CT scans in detecting asbestosis [14]. Finnish investigators also showed a significant positive correlation with frequencies of lung sounds and pulmonary fibrosis detected on HRCT [15]. Of course in industrial settings, in contrast to ER's and ICU's, neither CHF nor PN crackles are likely to be confounding variables.…”
Section: Discussionmentioning
confidence: 99%
“…Frequency distribution of lung sounds using computerized lung sound analyzer is significantly associated with interstitial lung fibrosis on high-resolution computed tomography (HRCT) scoring in patients with asbestos-related lung injury. The inspiratory crackles and high sound frequencies are associated with fibrotic changes to the lung while low sound frequencies were associated with emphysematous components of the asbestos-injured lung [ 91 ].…”
Section: Clinical Applications Of Lung Soundsmentioning
confidence: 99%